Odpowiedzi

2010-02-17T13:09:30+01:00
A)(x+1)(x+8)=(x+3)(x+5)
x²+8x+x+8=x²+5x+3x+15
x²+9x-x²-8x=15-8
x=7

b)(x-4)²-1=(x-3)(x-2)
(x-4)(x-4)=x²-2x-3x+6
x²-4x-4x+16=x²-5x+6
x²-8x-x²+5x=6-16
-3x=-10
x=3⅓

c)(x-2)²-x(x-4)=4(x-3)
(x-2)(x-2)-x²+4x=4x-12
x²-2x-2x+4-x²+4x=4x-12
x²-4x-x²+4x-4x=-12-4
-4x=-16
x=4

d)(x-9)(x-5)=x²+56-14x
x²-5x-9x+45=x²+56-14x
x²-14x-x²+14x=56-45
0=11
równanie sprzeczne


e)x²-(x+3)(x+4)=x+20
x²-(x²+4x+3x+12)=x+20
x²-x²-4x-3x-12=x+20
-7x-x=20+12
-8x=32
x=-4



f)(x-1)(x+1)-x(x+2)-1=2(x+1)
x²+1x-1x-1-x²-2x-1=2x+2
-2x-2x=2+2
-4x=4
x=-1



g)4(x+2)²=(2x-1)(2x+1)-2(2x-1)
4(x²+4x+4)=4x²+2x-2x-1-4x+2
4x²+16x+16=4x²-1-4x+2
4x²+16x-4x²+4x=2-1-16
20x=-15
x=-3/4